“Diagnostico de la actividad piscícola en la provincias de mariscal cáceres, huallaga y bellavista” - Sánchez Laurel, Carlos Fernando (2008)
The. Fish farming is the study of fish and that form part of the aquac between itself, in general called depending on the species or the family. "Level ~;;:;;." industrial fish farming facilities are known as fish farms or fish farms, although they are terms into disuse because of the diversification that has been growing, in tanks, ponds, floating cages, etc. Fish is one of the most important proteins of animal origin, available for human consumption in the Amazon and cheap. In this reason, fish farming is called to play an important role in this region as well as lower the envelope use of fishing on the aquatic resources, means an opportunity to generate jobs as well as create an environment for recreation and commercial fishing. It great potential that has currently the aquaculture in the Peru and basically in the Amazon, is based in explore the features of new espe...